Assembly of Slx4 signaling complexes behind DNA replication forks. (25th June 2015) - Balint, Attila; Kim, TaeHyung; Gallo, David; Cussiol, Jose Renato; Bastos de Oliveira, Francisco M; Yimit, Askar; Ou, Jiongwen; Nakato, Ryuichiro; Gurevich, Alexey; Shirahige, Katsuhiko; Smolka, Marcus B; Zhang, Zhaolei; et al.
Abstract Obstructions to replication fork progression, referred to collectively as DNA replication stress, challenge genome stability. In Saccharomyces cerevisiae, cells lacking RTT107 or SLX4 show genome instability and sensitivity to DNA replication stress and are defective in the completion of DNA replication during recovery from replication stress. We demonstrate that Slx4 is recruited to chromatin behind stressed replication forks, in a region that is spatially distinct from that occupied by the replication machinery. Slx4 complex formation is nucleated by Mec1 phosphorylation of histone H2A, which is recognized by the constitutive Slx4 binding partner Rtt107. Slx4 is essential for recruiting the Mec1 activator Dpb11 behind stressed replication forks, and Slx4 complexes are important for full activity of Mec1. We propose that Slx4 complexes promote robust checkpoint signaling by Mec1 by stably recruiting Dpb11 within a discrete domain behind the replication fork, during DNA replication stress.